(3aJM eUQs - (3fhQ GdOjf CMeO Hf Ydj Hf CMeO Hf RfHd GdQeGd GdeMdj GdeUQj GdTGaYj, GHf RfHd,J (B980 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi cd MGd hGdUdGI hGdSdGe Ydi GdfHi eMeO hBdg hUMHg hSde hHYO abO SCd GdabjQ Edi Gddg JYGdi GdTjN eMeO GdRHfdi GdQeGd Cf jhabg Gddg JYGdi hjYjfg Cf jDda SjQI Gdedc GdCTQa GdSdWGf GdZhQi eY GdSdWGf Sdje NGf heG hbY dge ef GdMQhH hGdbJd hs
(3BNQgG (B:s
(3Je HMeO Gddgq s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B174 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B196s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs